2018
DOI: 10.1093/poq/nfy005
|View full text |Cite
|
Sign up to set email alerts
|

Ideologues without Issues: The Polarizing Consequences of Ideological Identities

Abstract: The distinction between a person’s ideological identity and their issue positions has come more clearly into focus in recent research. Scholars have pointed out a significant difference between identity-based and issue-based ideology in the American electorate. However, the affective and social effects of these separate elements of ideology have not been sufficiently explored. Drawing on a national sample collected by SSI and data from the 2016 ANES, this article finds that the identity-based elements of ideol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
237
2
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(296 citation statements)
references
References 29 publications
21
237
2
12
Order By: Relevance
“…For instance, right-leaning individuals' WTD against left-leaning contents or individuals was less pronounced than left-leaning individuals' WTD against right-leaning contents or individuals. Additionally, both groups of participants tended to be more reluctant to defend arguments with right-leaning conclusions than those with left-leaning onesan interesting finding suggesting ideological self-censoring among participants (Bar Tal, 2017;Maroja, 2019). Moreover, while we found that factions within the leftleaning side of the political spectrum are sometimes hostile against each other too, we could not detect a similar phenomenon among right-leaning subjects.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…For instance, right-leaning individuals' WTD against left-leaning contents or individuals was less pronounced than left-leaning individuals' WTD against right-leaning contents or individuals. Additionally, both groups of participants tended to be more reluctant to defend arguments with right-leaning conclusions than those with left-leaning onesan interesting finding suggesting ideological self-censoring among participants (Bar Tal, 2017;Maroja, 2019). Moreover, while we found that factions within the leftleaning side of the political spectrum are sometimes hostile against each other too, we could not detect a similar phenomenon among right-leaning subjects.…”
Section: Discussioncontrasting
confidence: 73%
“…Moreover, even advocates of misguided minority views might be epistemically beneficial in challenging and/or motivating those holding the accurate views to articulate and keep in sight the reasons for their views (Longino, 2002, p. 131;Peters 2019). An absence of and/or discrimination against misguided minority positions may also increase the probability that subjects come to hold widely shared correct views without being able to properly defend them (Maroja, 2019).…”
Section: Epistemic Costsmentioning
confidence: 99%
“…It is unsurprising then, that some beliefs and attitudes are harder to change than others, such as those that have strong political implications [29,35,43]. Attitudes towards the implementation of policies are one such area that may be harder to shift, especially given that public support for some policies is increasingly influenced by political identities [44], for example, around climate change, abortion, and gun control. Yet, even so, a large literature in persuasion psychology shows that the framing of information can significantly alter the value and weight people attach to their beliefs about policies and their effectiveness [45].…”
Section: Introductionmentioning
confidence: 99%
“…These may sometimes align, but they are not the same thing, as it is possible for people to show loyalty to a party in the absence of holding strong ideological principles (Barber & Pope, 2018) or adhere to an ideology in the absence of strong or consistent issue positions (Mason, 2018a). Political coalitions do shift over time as parties become stronger or weaker relative to their opponents, perhaps in part due to differential strength in tribal motivations of group members (which are also shifting across time and political context; see e.g., Wheeler et al, 2020).…”
Section: Political Asymmetriesmentioning
confidence: 99%